2011 Triennial Surveillance Review : External Study. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
External study prepared by John Palmer, Chair, Toronto Leadership Centre, former Superintendent, Office of the Superintendent of Financial Institutions, Canada, former Deputy Managing Director Monetary Authority of Singapore, former Canadian Managing Partner of KPMG and Yoke Wang Tok, Former Senior Advisor to the IMF Executive Director representing ASEAN, Nepal, Fiji and Tonga and former Principal Economist, Monetary Authority of Singapore: This report aims to provide an independent view of how the Fund is discharging its multilateral surveillance responsibilities, in particular its contribution to global financial stability and crisis prevention, working in coordination with other relevant international groupings/institutions such as the FSB and BIS. As we emerge from the global financial crisis (GFC), the Fund has regained much of its credibility and relevance. The GFC caught many, including the IMF, by surprise. Since then, the Fund has done considerable self-analysis and taken active steps to strengthen its surveillance and policy advice and to improve traction with policy makers. The IEO report on the Fund's performance in the run-up to the financial and economic crisis identified various shortcomings that needed to be addressed. One of its key findings was the inability of the Fund to connect-the dots, to deliver hard-hitting messages and the difficulty experienced by the Fund in thinking beyond mainstream/official views. Many of the IEO's findings have relevance to this review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet